A moderated mediation analysis of depression and age on the relationship between resilience and frailty among HIV-positive adults - Lijun Meng; Dan Chen; Peiwu Hu; Meng Yao; Cui Zhou; Xingli Li (Frontiers Media S.A., 2023)
BackgroundGiven the continuing challenges frailty poses among people living with human immunodeficiency virus (HIV) (PLHIV), accumulating evidence suggests that frailty is linked to psychological factors. However, the mutual influences of resilience, depression, and frailty have not yet been clarified. This study aimed to identify the potential mechanistic pathway through which psychological factors mitigate frailty.MethodsData were collected from June to August 2019 by trained investigators through face-to-face interviews with 375 HIV-positive Chinese adults. Each participant completed structured questionnaires to collect data in respect of their socio-demographic characteristics, and levels of frailty, depression, and resilience. These assessment measures included a self-designed questionnaire, the Tilburg Frailty Indicator (TFI), the 10-item Center for Epidemiological Studies Depression Scale (CES-D-10), and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). SPSS PROCESS macro was used to analyze the mediation and moderated mediation models.ResultsThe overall prevalence of frailty was 26.4%, and the prevalence of frailty among older and younger adults living with HIV was 22 and 31.4%, respectively. Mediation analysis showed that an association between resilience and frailty was mediated by depression, whereas resilience did not mediate the relationship between depression and frailty. Compared to physical frailty, depression was a stronger mediator of resilience to psychological frailty. We further found that age moderated the indirect effect of resilience on psychological frailty, with resilience being a stronger negative predictor of depression and depression being a stronger positive predictor of psychological frailty for older PLHIV than for younger PLHIV.ConclusionLower levels of resilience and greater levels of depression may be significant risk factors for frailty among PLHIV. Levels of resilience influenced frailty directly and frailty was indirectly affected by depression. Therefore, it is recommended that PLHIV, especially older patients, should be encouraged to establish positive psychological coping strategies to slow the progression of frailty.